Enhancing Red-Chili (Capsicum annuum L.) Growth Using Black Soldier Fly (Hermetia illucens) Probiotics as Carrier - Hadid, Mulyana; Sanjaya, Yayan; Kusnadi (Universitas Atma Jaya Yogyakarta, 2025)
Red chili (Capsicum annuum L.) is a crucial horticultural commodity in Indonesia, necessitating expansion to meet the growing food demands. The formulation of carriers with probiotics is a promising solution for improving red chili growth. This study examines how the combination of carriers containing bacteria and Trichoderma from the intestines of Hermetia illucens larvae affects the growth of red chili cultivar Lembang-1. The research method used a Randomized Block Design (RBD) with six treatments. The treatment consisted of a group with the addition of a kaolin carrier with bacteria and Trichoderma (BTrK), a talc carrier with bacteria and Trichoderma (BTrT), a zeolite carrier with bacteria and Trichoderma (BTrZ), and a control group without a carrier (KtC), a positive control (K(+)), and a negative control (K(-). The Least Significant Difference (LSD) test showed that the addition of carriers affected increasing plant height and the number of branches compared to the negative control. Specifically, BTrK demonstrated the highest number of leaves and branches. The result concluded that adding carriers with probiotics from the intestine isolate of BSF larvae contributes to the improved growth of red chili. The implementation of carrier addition with probiotics is considered to be a sustainable strategy in agriculture.